Effect of nitrogen supplementation on urea recycling in steers consuming corn-based diets - Drake, D.W.; Jones, M.L.; Anderson, David E.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Nitrogen absorbed in the small intestine of cattle can be recycled to the rumen and incorporated into microbially synthesized amino acids. This is an advantage when dietary protein is low or when ruminally available nitrogen is limited by poor ruminal protein degradation. In a survey, consulting feedlot nutritionists reported that 83% of their clients used ethanol coproducts in finishing diets. Ruminal availability of nitrogen in dried distillers grains with solubles is low (i.e., 25% of total nitrogen). Thus, urea recycling may be of greater relative importance when distillers grains are used to supplement protein to cattle. The goals of our study were to better predict the amount of urea recycled by growing cattle fed corn-based diets supplemented with dried distillers grains with solubles or urea and quantify use of recycled urea by ruminal microbes.
Keywords: Beef; Nitrogen; Urea; Steers; Corn